HUMANITARIAN SUPPLY CHAIN RISK MANAGEMENT (HSCRM) - Viagi, Arcione Ferreira; Panizzolo, Roberto; Crescenzo, Alberto Maria de; Viagi, Felipe Monteiro (Revista Ciências Exatas, 2023)
Natural disasters or complex emergencies affect millions of people every year and cause losses such as the damage to buildings, infrastructure and natural resources. Because of this, humanitarian organizations acting increasingly pro-actively to be efficient and effective in responding to emergencies worldwide. The management of the supply chain has been used to help in taking preventive action, creating an integrated logistics structure which reduced the response time. This paper proposes a framework with a new stage in the disaster management cycle, making risk management proactively planning and execution and control of the process organizations to act effectively with catastrophic events.